POLITICAL EMPOWERMENT OF RURAL WOMEN IN GRAM PANCHAYATS (A STUDY WITH REFERENCE TO GRAM PANCHAYATS IN CHAMPAWAT DISTRICT OF UTTARAKHAND) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
POLITICAL EMPOWERMENT OF RURAL WOMEN IN GRAM PANCHAYATS (A STUDY WITH REFERENCE TO GRAM PANCHAYATS IN CHAMPAWAT DISTRICT OF UTTARAKHAND)